Design and assessment of a web-based educational electronic system for non-practical nursing skills development among nursing students - Abedi, Ali; Shamsabadi, Ahmadreza; Shoraka, Hamid Reza; Hosseini, Mohammad; Khorashadizadeh, Fatemeh; Rostami, Rohalla; Namazinia, Mohammad (BMC medical education, 2025)
Background Despite the importance of non-practical nursing activities, there is currently a lack of a suitable framework for their use among nurses and nursing students in Iran. This study aimed to design, implement, and evaluate a web-based educational electronic system for developing non-practical nursing skills (ESNPNSD). Methods This sequential methodological study was conducted in three phases: (1) identifying the Minimum Data Set (MDS) elements, (2) designing, developing, and implementing the system, and (3) evaluating the ESNPNSD. The system was assessed by 72 nursing students from two academic semesters, selected through convenience sampling. Following validation by experts during a Delphi phase, the ESNPNSD was developed and evaluated using the User Experience Questionnaire (UEQ). The UEQ scores ranged from − 3 to + 3 and included categories of normal, positive, and negative evaluations. Data were analyzed using SPSS version 18. Ethical considerations were fully observed. Results In the first phase, 136 items were identified across 12 categories. After formal and content validity checks, 68% and 55% of the items achieved content validity coefficients of 1 and 0.87, respectively, qualifying them for inclusion in the system. The Cronbach’s alpha score for all items in the system was 0.95. The ESNPNSD system scored averages of 1.75 for attractiveness, 1.46 for dependability, 1.58 for efficiency, 1.74 for novelty, and 1.23 for stimulation. Conclusion The ESNPNSD has the potential to support the development of non-practical nursing skills and facilitate patient safety by providing structured educational resources and interactive learning experiences. However, further studies with objective assessments of learning outcomes are needed to validate its impact comprehensively. Clinical trial number not applicable.